The effects of video content within e-participation platforms on behavioural intention : an analysis of new forms of digital political engagement of young adults in Germany on the example of the e-participation app “FollowTheVote” - Heinz, Maren (2022)
The nature of citizens' political engagement in Europe is changing. In particular, young citizens are witnessing a decline in voter turnout, political party membership, and interest in politics. With 84% of young people spending a significant amount of time on social media, e-participation tools could use some social media engagement mechanisms to their own advantage. Therefore, this study aims to analyze the effects on the acceptance and use of the E-Participation platform FollowTheVote in Germany. In particular, the effect of video content on behavioural intention is measured. For this purpose, a quantitative panel study, over seven days, was conducted with a group of 58 prototype testers. The treatment group was exposed to video content from day three onwards, whereas the control group was exposed to the same written form of content over seven days. The research framework is based on the Technology Acceptance Model which has been extended to fit the context of e-participation platforms. The results indicate that Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment have a statistically significant positive effect on the Behavioural Intention of the e-participation platform FollowTheVote. However, the implementation of video content has shown no statistically significant effect on the acceptance and use of the platform. This might be explained by the relatively small sample size, decreasing the statistical power. As the topic of study is relatively young, this research strongly contributes to the validation of the market potential and media innovation within the sector of e-participation platforms in Germany.